Menin Inhibitors in Acute Myeloid Leukemia: Clinical Integration, Resistance, and the Path Beyond Monotherapy - Tina Y. Zhang; Shyam A. Patel; Talha Badar (Cancers, 2026)
Advances in the molecular characterization of acute myeloid leukemia (AML) in recent decades have driven the development and clinical introduction of several targeted therapies, and menin inhibitors are the most recent additions to the therapeutic arsenal of AML treatments. The KMT2A and NPM1 loci have been the focus of intense investigation over the past two decades because of their well-established roles leukemogenesis, particularly in pre-clinical models of AML involving human xenografts. The ability of KMT2A and NPM1 aberrancies to drive and sustain leukemogenesis has provided a strong rationale for the development of therapeutic strategies to disrupt these molecular pathways. Menin inhibitors preferentially eliminate clones harboring KMT2A rearrangements or NPM1 mutations due to the dependence of these leukemia cells on the menin–KMT2A complex and its downstream HOXA9/MEIS signaling to sustain leukemic self-renewal and disease maintenance. In this review, we discuss the biological rationale for menin–MLL disruption in patients with acute leukemia with KMT2A rearrangement or NPM1 mutation. We explore data from the landmark AUGMENT-101 and KOMET-001 trials, which have led to regulatory approval of revumenib and ziftomenib for select patients. We also explore cutting-edge studies using menin inhibitors in combination strategies, including data from KOMET-007. The evidence supporting combination approaches remains based on early-phase, single-arm trials with relatively short follow-up, and longer-term and comparative data are needed to define their clinical benefit. We highlight resistance mechanisms that have emerged from the use of contemporary menin inhibitors and efforts aimed at addressing this resistance, with a focus on emerging clinical data on enzomenib and bleximenib. Finally, we discuss prospects on the putative role of menin inhibitors in the measurable residual disease (MRD)-positive and maintenance settings in AML. Menin inhibitors have successfully transitioned from biological proof-of-concept to approved targeted therapy, and future advances will depend on rational front line combination strategies, MRD-guided treatment, post-transplant maintenance strategies, and therapeutic sequencing informed by mechanisms of resistance.